2011
DOI: 10.1016/j.jmaa.2011.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Geometry of the copositive and completely positive cones

Abstract: The copositive cone, and its dual the completely positive cone, have useful applications in optimisation, however telling if a general matrix is in the copositive cone is a co-NPcomplete problem. In this paper we analyse some of the geometry of these cones. We discuss a way of representing all the maximal faces of the copositive cone along with a simple equation for the dimension of each one. In doing this we show that the copositive cone has faces which are isomorphic to positive semidefinite cones. We also l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 14 publications
2
28
0
Order By: Relevance
“…, m) is impossible. Very recently, Zhang [29] showed that the CPP cone with dimension not less than 5 is not facially exposed, i.e., some of its faces are non-exposed (see also [6,13] for geometric properties of the CPP cone). Thus, our framework using COP(co(K ∩ J), Q 0 ) is more general than the work using (2) in [1,2,3,4,19].…”
Section: Relations To Existing Workmentioning
confidence: 99%
See 3 more Smart Citations
“…, m) is impossible. Very recently, Zhang [29] showed that the CPP cone with dimension not less than 5 is not facially exposed, i.e., some of its faces are non-exposed (see also [6,13] for geometric properties of the CPP cone). Thus, our framework using COP(co(K ∩ J), Q 0 ) is more general than the work using (2) in [1,2,3,4,19].…”
Section: Relations To Existing Workmentioning
confidence: 99%
“…. , m) and m. Conversely, we can construct any face J of coK by (12), (13) and (14) as we shall present next. Since all Q pj ∈ V (j = 1, .…”
Section: The Hierarchy Of Copositivity Conditionmentioning
confidence: 99%
See 2 more Smart Citations
“…A cone is facially exposed if all of its faces are exposed. Although every extreme ray of CP d is exposed [59], it remains unknown whether CP d is facially exposed. In the case of COP d , the extreme rays corresponding to |ii ii| are not exposed [59], implying that PSD d + N d (the set of DEWs for PPTDS states) is not facially exposed.…”
Section: B Exposednessmentioning
confidence: 99%